If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(1y+8)-5=4(y+2)-6y
We move all terms to the left:
-(1y+8)-5-(4(y+2)-6y)=0
We add all the numbers together, and all the variables
-(y+8)-(4(y+2)-6y)-5=0
We get rid of parentheses
-y-(4(y+2)-6y)-8-5=0
We calculate terms in parentheses: -(4(y+2)-6y), so:We add all the numbers together, and all the variables
4(y+2)-6y
We add all the numbers together, and all the variables
-6y+4(y+2)
We multiply parentheses
-6y+4y+8
We add all the numbers together, and all the variables
-2y+8
Back to the equation:
-(-2y+8)
-1y-(-2y+8)-13=0
We get rid of parentheses
-1y+2y-8-13=0
We add all the numbers together, and all the variables
y-21=0
We move all terms containing y to the left, all other terms to the right
y=21
| x-42=76 | | |9-3n|=3 | | x-40=-63 | | 70-x=4 | | 14-w=16 | | x+57=16 | | 2x2+19x+40=-2x | | 6x+7=26,1 | | 6-4x=-2x-6 | | 4=5x=-41 | | 6-4x=2x-7 | | 4d−6=30d= | | -3x+4=18-5x | | -6=3x=-39 | | 21=5v-2v | | -7x+9=75 | | 18+x=94 | | -7x=9=-75 | | 5x−3=15 | | 2.25n=90,n | | 10x+33=100 | | 5x−3=15, | | 6x+7(4x+6)=-94 | | 2x−110=390. | | 2x+7/3=8,7 | | -4(-x-5)=42 | | t/3−22=-13 | | 5x-8 = 14 | | w=-1+1/5 | | -9u-31=-4(u-1) | | -9-4x=35 | | x/11-13=27 |